The world economy and the Euro Area: Broad-based upswing - Ferdinand Fichtner; Guido Baldi; Christian Dreger; Hella Engerer; Stefan Gebauer; Malte Rieth (DIW Economic Bulletin, 2017)
This year and next, global GDP will grow more strongly than expected. The growth rate should be just under four percent. In developed economies, the continuing improvement in the job market situation will drive consumption. Corporate investment activity will also gain momentum. Over the forecast horizon, a slowly rising inflation rate and somewhat tighter monetary policy will gradually slow private consumption down. Emerging countries are able to maintain somewhat more robust growth. Production is expanding again in China. In Brazil and Russia, stabilizing prices of raw materials and decreasing inflation rates are supporting economic momentum. Uncertainty about the US government's economic policy and the geopolitical conflict involving North Korea are current risks for the world economy.
Keywords: 330; Internationale Wirtschaft; Wirtschaftslage; Konjunktur; Wirtschaftsprognose; Eurozone